The relationship between professional identity and professional development among special education teachers: a moderated mediation model - Yueming Pi; Minjie Ma; Aixin Hu; Tingzhao Wang (BMC Psychology)
Abstract The professional development of special education teachers has received increasing attention in recent years, and identity has been identified as a protective factor in this context. However, only a limited amount of information is available regarding the potential mediators and moderators of this relationship. A major objective of this study was to determine (a) whether self-efficacy mediates the relationship between professional identity and professional development and (b) whether perceived social support moderates the indirect relationship between professional identity and professional development among special education teachers. A total of 2668 special education teachers participated in this study and completed measures relating to their professional identity, self-efficacy, perceived social support, and professional development. The study found that (1) professional identity is significantly and positively related to the professional development of special education teachers, while self-efficacy and perceived social support are similarly positively related to their professional development; (2) the relationship between professional identity and professional development is partially mediated by teachers' self-efficacy; and (3) perceived social support moderates the indirect effects of professional identity on special education teachers' professional development via self-efficacy. Based on the findings of this study, it appears that high perceived social support may be a protective factor concerning the professional development of special education teachers with low self-efficacy since these special education teachers appear to require more professional development.